Mobile Microlearning in English as A Foreign Language: Designing Daily Task Cycles for Retention - Panji Tanashur; Dimas Pujianto; Eka Nurindah Sari; Rodearta Purba; Rae Shella Tivani Mareta (LPPM Universitas Bumigora Mataram, 2026)
Mobile microlearning has become an increasingly relevant pedagogical approach in the English as a Foreign Language (EFL) context, particularly where learners exhibit fragmented study patterns and rely heavily on mobile devices for academic support. Although microlearning is widely adopted, its mechanisms for supporting long-term retention remain insufficiently theorized. Research tends to emphasize engagement and convenience rather than cognitively grounded task design. This study aims to examine the effects of three mobile microlearning task cycles, called spacing, retrieval practice, and mixed-strategy interleaving, on long-term retention among Indonesian EFL learners at Universitas Negeri Manado (UNIMA). A quasi-experimental pretest-posttest design was conducted with 98 Indonesian EFL learners at Universitas Negeri Manado. Participants were assigned to three treatment groups representing spacing, retrieval practice, and mixed-strategy interleaving task cycles and received daily microlearning activities via WhatsApp for eight weeks. Data were collected through pretests, posttests, delayed retention tests, learning analytics, and semi-structured interviews. Quantitative data were analyzed using inferential statistics, while qualitative interview data were subjected to thematic analysis. The results indicate that mixed-strategy interleaving cycles produced significantly higher long-term retention compared to single-strategy cycles, along with more stable weekly participation. Additionally, the qualitative findings indicate that daily micro tasks reduce cognitive load, foster autonomous learning habits, and increase learners’ willingness to engage in incremental study. These findings suggest that the effectiveness of mobile microlearning depends not merely on brevity but on integrating cognitive learning principles into task design, with important implications for EFL pedagogy, digital task design, and mobile learning integration.